2006
DOI: 10.1892/0891-6640(2006)20[1355:pouabd]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Unilateral and Bilateral Deafness in Border Collies and Association with Phenotype

Abstract: Background: Congenital sensorineural deafness (CSD) occurs in Border Collies, but its prevalence and inheritance are unknown. This study estimated the prevalence of CSD in Border Collies and investigated its association with phenotypic attributes linked to the merle gene, including coat pigmentation and iris color.Hypothesis: Deafness in Border Collies is associated with pigmentation patterns linked to the merle gene. Animals: A total of 2597 Border Collies from the United Kingdom. Methods: A retrospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…In total, there were more unilaterally deaf individuals (11.1%) than bilaterally deaf dogs (4.9%). This is in accordance with the results of other studies in which the frequency of unilaterally affected animals was generally higher than that of bilaterally deaf animals (Platt et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…In total, there were more unilaterally deaf individuals (11.1%) than bilaterally deaf dogs (4.9%). This is in accordance with the results of other studies in which the frequency of unilaterally affected animals was generally higher than that of bilaterally deaf animals (Platt et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The suggestions for inheritance of deafness in Dalmatians include a dominant gene with incomplete penetrance, double dominant genes, or multifactorial recessive genes (Strain et al, 1992). Previous studies have identified statistically significant associations between deafness and a blue iris colour and white coat pigmentation (Strain, 2004;Platt et al, 2006). In the present article the occurrence was higher in dogs with one or two blue eyes.…”
Section: Discussionmentioning
confidence: 45%
“…We found unilateral deafness in 1 and bilateral deafness in 2 Boxers. Other studies that have evaluated the incidence of deafness showed a higher incidence of unilateral deafness compared to bilateral deafness in different breeds, such as Border Collies (2.3% unilateral and 0.5% bilateral) (Platt et al 2006), Bull Terriers (9.9% unilateral and 1.1% bilateral) (Strain 2004), Australian cattle dogs (12.2% unilateral and 2.4% bilateral) (Strain 2004), English Setters (12.7% unilateral and 2.4 bilateral) (Strain 1996) and English Cocker Spaniels (7% unilateral and 1.8% bilateral) (Strain 1996). The fact that this report found more bilateral deafness than unilateral, when other published reports, studying other breeds, found a higher prevalence of unilateral than bilateral, is certainly the result of the small sample size.…”
Section: Discussionmentioning
confidence: 89%
“…The fact that this report found more bilateral deafness than unilateral, when other published reports, studying other breeds, found a higher prevalence of unilateral than bilateral, is certainly the result of the small sample size. Deafness in dogs is frequently associated with altered expression of pigment genes, such as piebald and merle (Strain et al 2009), and several prior studies have identified statistically significant associations between deafness and a blue iris colour and white coat pigmentation (Strain 2004, Platt et al 2006, Famula et al 2007). Since not all dogs with piebald are deaf or have blue eyes, it can be argued that this variable outcome is the consequence of incomplete penetrance of a causative gene, or that one or more additional genes regulate the expression of the pigment gene (Strain 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation